Analisis Sikap terhadap Penggunaan Bahasa Daerah dan Bahasa Indonesia di Kekerabatan Keluarga Batak Simalungun - Artia Nirmala Sari Hutagaol; Junifer Siregar; Monalisa Frince Sianturi (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2021)
The purpose of this research to know: 1) describe positive attitudes and negative attitudes the of regional languages in the simalungun Batak Family kinship. (2) describe the factors that influence positive attitude and negative attitude indonesian usage and simalungun language in family kinship nagori bosi sinombah. AS for type of research used in this research is descriptive qualitative or non experimental, because in this study did not do control and manipulate research variables. Qualitative descriptive method is used to get word or action, quaalittive description not giving treatment, manipulation or independent variable change, but describes the condition as it is describe the object under study. This method is accompanied by analytical activities. The results of this study include: 1) There are positive and negative attitudes in Simalungun language towards family kinship in the nagori bosi sinombah, 2) about the factors that influence the family’s Indonesian attitude Bosi sinombah consicts of two factors, namely internal factors and ecternal factors. First, on internal factors,there are there is nationalis ntionl language contact on statement 18,educational factors on statements 18 and 19,factors of work of economic status that affect the attitude of speaking simalungunan and Indonesian in the family Nagoro Bosi Sinombah is found in statements 16 and 17. The emigration factor is contained in the statement 15. External factors, the ethnic identity factor is found in the statement 6,7,8,9,10,there are factors in the use of regional languages on the respondent’s answer statement 2 and 13, the bonding factor with traditional culture is found in the statement 13. Researchers see that family Bosi Sinombah has experienced developments in tearms of education and this affects the language attitude of the family Nagori Bosi sinombah Dolok Silau District Simalungun Regency.